Monitoring of insects with public participation (MIPP; EU LIFE project 11 NAT/IT/000252): overview on a citizen science initiative and a monitoring programme (Insecta: Coleoptera; Lepidoptera; Orthoptera) - Mason, Franco; Roversi, Pio Federico; Audisio, Paolo; Bologna, Marco Alberto; Carpaneto, Giuseppe Maria; Antonini, Gloria; Mancini, Emiliano; Sabbatini Peverieri, Giuseppino; Mosconi, Fabio; Solano, Emanuela; Maurizi, Emanuela; Maura, Michela; et al. (Fragmenta entomologica, 2015)
The LIFE project “MIPP” - Monitoring of Insects with Public Participation (11 NAT/IT/000252) is focused on selected insect species (five Coleoptera, three Lepidoptera, one Orthoptera), all included in the annexes II and IV of the Habitats Directive (HD) 92/43/EEC. One important aim is a citizen science initiative where every person may become a citizen scientist and collect faunistic data on the above species throughout Italy. Another objective of the project MIPP is the development of standard methods for monitoring the conserva- tion status of the five target beetle species. One innovative method employed is a sniffer-dog (“Osmodog”), trained to find the rare and endangered hermit beetle, Osmoderma eremita, which lives in veteran, hollow trees. The dog detects the strong smell of mature peach produced by adult males and an odor produced by the larvae. Another objective of the project MIPP is the dissemination of topics such as HD, Natura 2000, importance of dead-wood, Life projects, insect monitoring and conservation.